Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan Media Kantong Ajaib pada Pembelajaran IPS - Risna Anggraini; Andriana Sofiarini; Aren Frima (Journal of Elementary School (JOES), 2023)
The purpose of this research is to determine student learning outcomes after the implementation of the jigsaw cooperative learning model. As for the type of research used, namely pre-ekperimental design. The population of class IV SD Negeri 41 Lubuklinggau for the 2023 Academic Year is 20 students and the sample taken is 20 students. For sampling using test techniques. The data collected after being analyzed using the z-test at a significant level of a 0,05 obtained = 9,76 = 1,64, so that it can be concluded that student learning in class IV SD Negeri 41 Lubuklinggau after the implementation of the jigsaw cooperative learning model significantly complete with an average volue of student learning outcomes of 83,60. Keywords : Elementary School, Jigsaw, Learning Outcomes, Social Studies Learning